Nepal, India, and China Economic-Diplomatic (NICED) Relationship - Kafle, Jagannath (Nepal, 2025)
The conference paper is based on the potential trilateral economic cooperation between immediate neighbour countries Nepal, India, and China. The study attempts to reveal Nepal’s economic diplomacy through geographic perspectives aiming to enhance the present mode of economic activities between Nepal, India, and China. The potential cooperations attempt to apply an integrated equitable approach to the ‘Nepal, India, and China Economic-Diplomatic Relation’ (NICED Relation), the central and peripheral power of different economic market centres within and between these countries. The economic-diplomatic relationship and development cooperation between participating countries depend on the degree of diplomatic relationship they adopt. This trilateral relationship should help better neighbourhood cooperation and mutual benefits for the entire regional ‘Protection (security), Peace, and Prosperity’ between these immediate neighbours.
Conference Proceeding of “Second National Economists’ Conference-2079”